Case Report: Complete AV block in two patients with a congenital absence of the right coronary artery: an unusual correlation - Lai, Ruihui; Sun, Shuai; Chen, Yanjun; Xu, Tan (Frontiers in Cardiovascular Medicine, 2025)
BackgroundCongenital absence of the right coronary artery (RCA) is an extremely rare coronary anomaly with a very low incidence in the general population. The prevalence of complete atrioventricular (AV) block also appears to be low. No previous reports have documented the coexistence of congenital absence of the RCA and complete AV block in the same patient.Case summariesCase 1 was a 52-year-old man with no significant past medical history who experienced syncope. The initial ECG revealed complete AV block with a non-specific ST-T segment. Coronary angiography showed mild, non-obstructive atherosclerosis in the dominant left circumflex artery (LCx), which continued along the anatomical course of the RCA. The patient underwent a dual-chamber pacemaker implantation for complete AV block. Case 2 was a 79-year-old man with a history of hypertension and coronary heart disease who presented with gradually worsening fatigue lasting 6 h. ECG showed complete AV block with a non-specific ST-T segment. Coronary angiography revealed an abnormal origin of the RCA arising from the distal portion of a dominant LCx, which retrogradely followed the course of a normal RCA to the base of the heart. The patient also underwent a dual-chamber pacemaker implantation for complete AV block.ConclusionThese two cases represent the first reported instances of complete AV block coexisting with congenital absence of the RCA, where the LCx supplied the territory of the RCA without evidence of myocardial infarction.